Spasmolytic Effect of Black Bile-reducing Plants from Lamiaceae: the correlation between Traditional Iranian Medicine and Pharmacological and Phytochemical surveys - Fatemeh Rostaminejad; Shiva Hemmati; Parmis Badr (Shiraz University of Medical Sciences, 2022)
The roots of Traditional Iranian Medicine (TIM) go back to thousand years ago. Based on TIM, black bile, one of the four humors within the body, is the concentrated part of the blood representing a cold and dry quality. Black bile tends to deposit in tissues, leading to diseases such as spasm, which is a painful paralysis-like immobility condition. One of its possible causes is muscle dehydration, resembling the dryness caused by dominance of black bile. In TIM, several medicinal plants are claimed to be effective in the regulation of black bile; among them, the presence of the Lamiceae family is very notable. In this review, the relationship between spasm as one of the symptoms of increasing black bile in the body was discussed. Also, the compounds reported in the black-bile eliminating plants have been found in the literature. The majority of them were from monoterpenes and sesquiterpenes such as citral, carvacrol, fenchone and pulegone in the essential oil of black bile reducing plants. The main compounds properties of black bile reducing plants can be used to orient quantitative system pharmacology models in further studies. Please cite this article as: Fatemeh Rostaminejad, Shiva Hemmati, Parmis Badr. Spasmolytic Effect of Black Bile-reducing Plants from Lamiaceae: the correlation between Traditional Iranian Medicine and Pharmacological and Phytochemical surveys. Trends in Pharmaceutical Sciences. 2022;8(4):233-242. doi: 10.30476/TIPS.2022.96146.1157